Development of nano-material (Nano-Silver) in electronic components application - Mazlan Mohamed; Mohd Sukhairi Mat Rasat; Anizah Kalam; Abdullah, N.R; Huck-Soo Loo; A.M. Mustafa Al Bakri; M.S. Abdul Aziz; M.S. Abdul Aziz; C.Y. Khor; Mohammad Amizi Ayob (2013)
This paper presents the development of nano-material in electronic components especially in Plastic Leaded Chip Carrier (PLCC) application. The effect of nano-material in Plastic Leaded Chip Carrier (PLCC) will improve thermal resistance as well thermal performance in electronic application. This research is using three dimensional numerical analysis of heat and fluid flow in computer and 3D model of microprocessors is built using GAMBIT and simulated using FLUENT software. The study was made for several microprocessors arranged in line under different types of material, inlet velocities and package (chip) powers. The result are presented in terms of average junction temperature and thermal resistance of each package. The juction temperature is been observed and it was found that the junction temperature of the microprocessors is not exceed 70 C. It also found that the junction temperature of the microprocessors is not exceed 70 C. It also found that the application of nano-material in PLCC play important rolesto control and manage the junction temperature. The strengh of CFD software in handling heat transfer problems is proved to be excellent